Geografía por venir Questiones, opiniones, debates - DI CIONE, Vicente Comp. (COOPERATIVA EDITORA UNIVERSITARIA, 1997)
CONTENIDO : SANTOS, Milton; WADDELL, Eric; KONINCK, Rodolfo de; BRUNEAU, Michel; BRUNET, Roger; CLAVAL, Paul; FLIEDNER, Dietrich; HULBERT, Francois; LAGAREC, Daniel; LEVY, Jacques; MCGEE, Terence G.; RACINE, Jean-Bernard